Application Dictionary of Scientific Plants and Animals Android-Based Algorithm Using Jaro Winkler Distance - Rasna, Rasna; Rosiana Dewi, Ni Wayan Emmy; Bani, Alexius Ulan; Lamsir, Seno; Nugroho, Fifto (International Journal of Engineering, Science and Information Technology, 2025)
The dictionary is a kind of reference book composed of abjad and contains terms of terms and their meanings. Dictionaries are needed in education to figure out the word or term you want to know its meaning. In education, it is found in many terms, for example, in the biological sciences. In biology, there is the term a scientific term that must be known to every student, especially those who pursue the field of biology. The scientific term, or scientific name, is the Latin name of plants and animals and is one of the critical discussions in the biology field contained in the course curriculum of elementary school, junior high school, and senior high school lectures. The field of biology is the subject of the taxonomy of plants and animals, and each student is required to know the Latin of every plant and animal. This is because plants and animals in the world of biology are known to scientists with scientific language. In this research, the author applies the scientific language dictionary of plants and animals using an algorithm based on the android Jaro Winkler distance. Jaro Winkler's distance algorithm searches for the desired plants and animals. In this study, the plant names and scientific names are taken from existing books and journals. Each name consists of 1000 names of plants and animals, with each of the 500 names of plants and 500 animal names along with scientific language and the images, respectively. The system will generate output from the scientific names of plants and animals and be equipped with pictures and explanations. The results from this study use an algorithm called Jaro Winkler Distance to search for the names of the desired plants and animals by matching each character entered with the characters in the database.